Individual Preparedness and Response to Chemical, Radiological, Nuclear, and Biological Terrorist Attacks : a Quick Guide. - Davis, Lynn (RAND Corp., 2003)
Even people who consider themselves prepared to deal with common emergencies might not know what to do during a chemical, radiological, nuclear, or biological attack. This quick guide offers suggestions about how individuals can prepare for such attacks and what actions they can take during each type of attack to protect their own health and safety--and, possibly, their own lives.